Artificial intelligence challenges to education - Baskas, Antanas (Lietuvos matematikos rinkinys, 2002)
Paper discusses challenges to education called out by Educational delivery, Course management, Learning management and Authoring intelligence tutoring systems. Educational delivery systems – a software product or suite that facilitates the delivery of content or interaction by the web. Course management systems (CMS) – a software product that generally incorporates an educational delivery system for a topic (typically called a ``Course’’ in educational institutions and most often facilitated via asynchronous-based formats) and provides integrated tools for measuring outcomes and reporting progress for individual or groups of students. CMS systems are currently most popular for educational institutions that are inclined to think of on-line development as course-centric. Learning management systems (LMS) – a software product that provides learners an integrated view of all their active coursework and assignments in a ``syllabus’’ that spans multiple courses. LMS systems are most often found in large corporate training departments and corporate universities. Intelligent management systems art computer-based instructional systems with models of instructional content that specify what to teach, and teaching strategies that specify how to teach.